Effect of Feeding Fermented Catfish Pellets with Probiotics on Population Growth of Water Fleas (Daphnia Magna) - Cantika Glodia; Sucahyo (Britain International for Academic Research (BIAR) Publisher, 2022)
D. magna as feed has advantages: easy to digest, the size is in accordance with the larval mouth opening, has 42.65% protein in the form of nutrition, contains a number of digestive enzymes, does not degrade water quality and can be cultivated in bulk. In this study, commercial catfish pellets fermented with probiotics were used as feed for D. magna. The probiotic that is often used in aquaculture is EM4 (Effective Microorganism 4). EM4 is able to play a role in increasing protein levels and with the right dose, EM4 becomes the main determining factor in growth productivity. The purpose of this study was to determine the good duration of EM4 fermentation in population growth of D. magna. This study is an experimental study (CRD), using D. magna as a test animal, with 5 different treatments. The results of the density of D. magna which were given different treatments gave different results. The highest density was found in treatment 3 and the treatment that had the lowest density was in treatment 5. The results of the Nonparametric test (Friedman-Test) showed significant results (P=0.00<0.05). Significantly different treatments were in treatment 3 and 5, while treatment 2 and treatment 4 had no significant difference. The results of the study the highest specific growth rate obtained was in treatment 4 of 0.223%/day, then followed by treatment 3 of 0.211%/day, while other treatments were relatively lower. Thus, feeding in the form of catfish pellets fermented with EM4 on the population growth of Daphnia magna gave a significant effect on treatment 3 and treatment 5 with the highest specific growth rate in treatment 4.